2021
DOI: 10.1177/0300985821996671
|View full text |Cite
|
Sign up to set email alerts
|

Role of Periostin Expression in Canine Osteosarcoma Biology and Clinical Outcome

Abstract: Periostin is a matricellular protein important in regulating bone, tooth, and cardiac development. In pathologic conditions, periostin drives allergic and fibrotic inflammatory diseases and is also overexpressed in certain cancers. Periostin signaling in tumors has been shown to promote angiogenesis, metastasis, and cancer stem cell survival in rodent models, and its overexpression is associated with poor prognosis in human glioblastoma. However, the role of periostin in regulating tumorigenesis of canine canc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 85 publications
0
2
0
Order By: Relevance
“…The expression of this marker has been poorly investigated in canine-bearing tumors. Only two studies focusing on canine mammary tumors (22,23), one on squamous cell carcinoma and one on osteosarcoma, are present in the literature (24,25). One of the two studies regarding canine mammary tumors (22) demonstrated a positive correlation between the expression of POSTN in CAFs in mammary carcinomas, the tumor grade, and the expression of the Ki-67 proliferative antigen, suggesting a role of POSTN in the pathogenesis of canine mammary tumors as in humans.…”
Section: Introductionmentioning
confidence: 99%
“…The expression of this marker has been poorly investigated in canine-bearing tumors. Only two studies focusing on canine mammary tumors (22,23), one on squamous cell carcinoma and one on osteosarcoma, are present in the literature (24,25). One of the two studies regarding canine mammary tumors (22) demonstrated a positive correlation between the expression of POSTN in CAFs in mammary carcinomas, the tumor grade, and the expression of the Ki-67 proliferative antigen, suggesting a role of POSTN in the pathogenesis of canine mammary tumors as in humans.…”
Section: Introductionmentioning
confidence: 99%
“…3,5 Immunohistochemistry remains a mainstay for the diagnostic pathology, and several articles of the special issue describe the expression of novel immunohistochemical markers in canine tumors such as periostin in canine osteosarcoma and nestin in canine mammary carcinoma. 1,20 Correlation of these markers with follow-up data offers insights on the prognostic significance and potential clinical relevance of these markers. Immunohistochemistry was also used to study the immune cell microenvironment in an article on the role of mutated BRAF V595E in influencing the recruitment of regulatory T lymphocytes in canine urothelial carcinoma.…”
mentioning
confidence: 99%